2021
DOI: 10.3389/fneur.2021.700190
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the Minimal Clinically Important Differences for Sagittal Hip Range of Motion in Chronic Stroke Patients

Abstract: Many researchers have pointed out that decreased sagittal range of motion (ROM) in the affected hip joint is a common consequence of stroke, and it adversely affects walking performance and walking speed. Nevertheless, the minimal clinically important differences (MCID) in hip-related kinematic gait parameters post-stroke have not yet been determined. The present study aimed to define MCID values for hip ROM in the sagittal plane i.e., flexion–extension (FE), for the affected and unaffected sides at a chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…MCID is defined as "the smallest difference in score in the domain of interest which patients perceive as beneficial and which would mandate, in the absence of troublesome side effects and excessive cost, a change in the patient's management" (Jaeschke et al, 1989). This concept is common in the clinic and some studies have analyzed it in post-stroke gait for different joints in the sagittal plane such as the hip, where the MCID of the ROM for the affected side is about 5.81 • and for the unaffected side at around 2.86 • (Guzik et al, 2021), and the knee, where MCID of the ROM for the affected side is about 8.48 • and for the unaffected side at around 6.81 • (Guzik et al, 2020). Although PROM is related to the ROM studied in Guzik et al (2020Guzik et al ( , 2021, it is usually higher and no specific MCID was found for this population and measured in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MCID is defined as "the smallest difference in score in the domain of interest which patients perceive as beneficial and which would mandate, in the absence of troublesome side effects and excessive cost, a change in the patient's management" (Jaeschke et al, 1989). This concept is common in the clinic and some studies have analyzed it in post-stroke gait for different joints in the sagittal plane such as the hip, where the MCID of the ROM for the affected side is about 5.81 • and for the unaffected side at around 2.86 • (Guzik et al, 2021), and the knee, where MCID of the ROM for the affected side is about 8.48 • and for the unaffected side at around 6.81 • (Guzik et al, 2020). Although PROM is related to the ROM studied in Guzik et al (2020Guzik et al ( , 2021, it is usually higher and no specific MCID was found for this population and measured in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…This concept is common in the clinic and some studies have analyzed it in post-stroke gait for different joints in the sagittal plane such as the hip, where the MCID of the ROM for the affected side is about 5.81 • and for the unaffected side at around 2.86 • (Guzik et al, 2021), and the knee, where MCID of the ROM for the affected side is about 8.48 • and for the unaffected side at around 6.81 • (Guzik et al, 2020). Although PROM is related to the ROM studied in Guzik et al (2020Guzik et al ( , 2021, it is usually higher and no specific MCID was found for this population and measured in the literature. Neither was it found for lower limb joint strength.…”
Section: Discussionmentioning
confidence: 99%
“…The test battery in the current study is commonly used for evaluation of gait function in neurological patients and was extended to include a wearable inertial sensor system for a more thorough gait analysis. The kinematic and temporal outcome measures can be used to evaluate, e.g., gait asymmetry and reduced range of motion, which are important aspects of walking ability post-stroke [ 7 , 8 , 9 , 10 , 11 , 12 ]. However, the current study was based on a control group with normal walking ability, and the results needs to be verified in patients with neurological disorders, such as stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Kinematic data was then time-normalized over each gait cycle and variables were computed for each gait cycle for the pelvis and thorax segments and for the shoulder, hip, knee, and ankle joints. The variables were selected from kinematic and temporal variables earlier suggested for use in clinical gait analysis [ 26 ] and of interest for post-stroke analyses [ 7 , 8 , 10 , 11 , 12 ]. These variables were the peak flexion angle, peak extension angle, the range of motion (i.e., peak flexion to peak extension, RoM), and the stride frequency (number of gait cycles per second).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation